Alternative water resources quality assessment during flood disaster in Kuala Krai, Kelantan, Malaysia - Koh, Liew See (Tanjung Malim, 2021)
Alternative water resources quality assessment during flood disaster in Kuala Krai, Kelantan, Malaysia by Koh, Liew See